Implementing virtual presentations program in ESL classrooms / Isma Noornisa Ismail, Farina Nozakiah Tazijan and Suzana Ab Rahim - Ismail, Isma Noornisa; Tazijan, Farina Nozakiah; Ab Rahim, Suzana (Research Management Institute (RMI), 2012)
Every student's academic and professional success is partially reliant on communicative education as it is an essential competency for students across disciplines in higher education (Rubin & Morreales, 1996 cited in [1].Having impressive grades is simply not adequate as students with excellent academic records are burgeoning everywhere. Hence, they need to have the extra edge to compete and possessing an effective communicative skill is a must in the current situation. Alain de Botton, a writer was once quoted saying that "I passionately believe that it is not just what you say that counts, it is also how you say it- that the success of your argument critically depends on your manner of presenting it," [2] This highlights the impact of boasting a great communication skill and in addition to that, it also prepares students to be effective employees for the global work environment (l) cited in [2]. The fear of speaking in front of a group weighs as one of the principal reasons why many job seekers are rejected and also why thousands of employees in the US decline job promotions. Krannich [3] explains that the acceptance of a new position often requires promoted individuals to deliver a speech or presentation to their newly assigned supervisors and departmental co-workers, the matter which they dreaded the most.